Tanggung Jawab Marketplace Terhadap Penjualan E-book Bajakan Perspektif Wahbah Zuhaili: Studi Kasus pada Marketplace Shopee - Ade Yusrah Hasanah; Tetty Marlina Tarigan (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
Sales of pirated e-books are still found today, especially on the Shopee marketplace, which of course harms many parties. This article aims to analyze the form of marketplace responsibility for the sale of pirated e-books on the Shopee marketplace from Wahbah Zuhaili's perspective. This research uses empirical juridical research with a living case studies approach, statute approach and conceptual approach. Data was collected by interviews and document studies, then the data was processed and analyzed using qualitative methods. The results of this research show that Wahbah Zuhaili emphasizes the importance of responsibility in every aspect of muamalah, including for parties involved in buying and selling transactions on the marketplace. Shopee as a marketplace platform has a big responsibility in preventing and cracking down on the sale of pirated e-books. This responsibility includes active supervision of products sold and based on the prohibited goods policy, Shopee has taken firm action against sellers who are proven to be selling pirated e-books, such as deleting products, reducing seller's rights, blocking and suspending seller accounts. Wahbah Zuhaili's view explains that someone's copyright which is then distributed with the intention of making a profit is an injustice, and the pirate should be responsible for providing compensation or royalties to the owner of the work who has sacrificed great effort in preparing his work.